Knowledge and technology transfer in and beyond mineral exploration - Michaela Keßelring; Moritz Kirsch; Frank Wagner; Richard Gloaguen (Journal of Innovation and Entrepreneurship, 2023)
In natural sciences, mineral exploration has a high network centrality. For industries with high technological- and knowledge proximity, transfer effects are an important function for innovation. Despite the high level of proximity between mineral exploration and other natural sciences, scholars hardly examine transfers from and to mineral exploration. This paper analyzes obstacles and mechanisms of transfer effects in and from mineral exploration and finds answers on how to institutionalize knowledge and technology transfer (KTT). The study employs a qualitative research design. The underlying database consists of 16 expert interviews, from the fields of natural science. The results show that KTT between areas as diverse as mineral exploration, healthcare, and arts are possible. A lack of interdisciplinary exchange and rigid scientific structures is the main inhibitor of KTT. Before this study, evidence for KTT from and to smaller industries is mostly anecdotal. The study is among the few, which investigates KTT concerning functional transfer opportunities.
Keywords: 650; Knowledge transfer; Mineral exploration; Natural sciences; Technology transfer